TINGKAT KOMPETENSI PROFESIONAL PENYULUH PERTANIAN DI KECAMATAN TAMBANG KABUPATEN KAMPAR - Nur Wahyuni; Rosnita '; Roza Yulida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study is to 1) know extension implementation;2) analyze competence level of extension worker; and3) know problems to increase extension competence in Tambang Sub district Kampar Regency. The method used of this study was surveymethod,while Censuswas also used as the sampling technique. The number of respondents were 11 samples.In terms of analyzing the data, Scale of Liker's Summated Rating (LSR) was used. The implementation of  agriculture extension activities are regularly held on Saturday and Sunday. The overall level of competenceswere categorized as “competent” with the score 4.12. It is depicted from the  administrative competence, teaching, communication, behavior understanding, and maintainprofessionalism and for the program planning capacity, implementation, and evaluation were as “very competent”. The high level of those programs was program planning capacity with the score 4.45(13, 50 %) and the low level was maintain professionalism with the score 3, 58 (10, 86 %). Problem of extension in the increasing extension worker namely, limited of worker, and the lack of information media.   Keywords: Competence, Extension and Professional